Amulet 1: The stonekeeper - Kibuishi, Kazu, 1978- (New York : Graphix, 2008)
After moving to their ancestral home, Emily and Navin's mother is kidnapped by a tentacled creature in the basement that leads the children on a deadly chase into the magical world below their home.
Book Links (A.L.A.)
School Library Journal
Wilson's Children
3.9
3-6.
3-6
Keywords: Magic -- Comic books, strips, etc -- Juvenile fiction; Single parent families -- Comic books, strips, etc -- Juvenile fiction; Cartoons and comics; Fantasy; Magic -- Fiction; Single parent families -- Fiction; Comic books, strips, etc; Graphic novels; Magic -- Comic books, strips, etc -- Fiction; Single parent families -- Comic books, strips, etc -- Fiction; Fantastic fiction; Fantasy comic books, strips, etc; Graphic novels